Red rabbit - Grecian, Alex (Nightfire, Tor Publishing Group, 2023)
"Sadie Grace is wanted for witchcraft, dead (or alive). And every hired gun in Kansas is out to collect the bounty on her head, including bona fide witch hunter Old Tom and his mysterious, mute ward, Rabbit. On the road to Burden County, they're joined by two vagabond cowboys with a strong sense of adventure - but no sense of purpose - and a recently widowed school teacher with nothing left to lose. As their posse grows, so too does the danger. Racing along the drought-stricken plains in a stolen red stagecoach, they encounter monsters more wicked than witches lurking along the dusty trail. But the crew is determined to get that bounty, or die trying." --Goodreads.